Occupational Safety in Action: Assessing the Implementation and Impact of Safety and Health Management Systems - Prasetyo Soleh D (Journal of Chemical Learning Innovation, 2025)
Purpose of the study: The aim of this research is to determine the counseling, implementation, supervision, and supporting facilities for the Occupational Safety and Health management system. Methodology: The study population was all 2,341 students of State Vocational High School 3 Yogyakarta. The sample size was 342 students, determined using the Slovin formula. Random sampling was used. Data collection was conducted using a questionnaire. Validity was determined using expert judgment, while reliability was determined using the Cronbach's alpha formula. Main Findings: The results of the study showed that: Extension with a score of 67 (quite good), implementation 74 (good), supervision 69 (quite good), facilities 76 (good), culture 78 (very good). Novelty/Originality of this study: It can be used as self-evaluation material in following the teaching and learning process and as input that it is important to prioritize the correct implementation of Occupational Safety and Health in students.